Survey study on awareness and consciousness level of sustainability in dentistry - TAĞTEKİN, DİLEK; AKMANSOY, ŞÜKRÜ CAN; ALKAN, ELİF (My University, 2023)
The United Nations' 17 Sustainable Development Goals (SDGs) are vital for equitable global benefits and a healthier future. This study examines the awareness levels of individuals with and without clinical dentistry training using LimeSurvey Community Edition and SPSS (Version 28.0.1.). The survey, conducted between July 15, 2021, and January 1, 2022, had 1734 participants, excluding third-grade students due to differing clinical instruction. Dental students, dentists, specialty/PhD students, specialists, academicians, and health personnel were included. The dental questionnaire comprised 26 questions, with statistically significant differences (p<0.05) in 11 responses. Those with clinical dental education showed significant (p<0.05) positive responses to sustainability-related questions, but no significant difference (p≥0.05) in general sustainability statements. The study emphasizes the need to define fundamental steps to address the current lack of interest in Sustainability in Dentistry and suggests integrating sustainability topics into the dental curriculum. Encouraging such practices can have a global impact, aligning with the SDGs. Educating dentistry professionals on sustainability will contribute to achieving these goals and benefitting present and future generations.
Keywords: Dentistry; Ecology; Sustainable Development; Survey